Hello

ln ( (e^x+1) / (x^3 + x^2) ) needs to be verified

So here's what I got:

= ln ( (e^x+1) / (x^3 + x^2) )

= ln (e^x+1) - ln (x^3 + x^2)

= (x+1) ln e - ln ((x^2(x+1))

-can't get past this point.

Printable View

- Nov 5th 2007, 03:04 AMGAdamsLog equation
Hello

ln ( (e^x+1) / (x^3 + x^2) ) needs to be verified

So here's what I got:

= ln ( (e^x+1) / (x^3 + x^2) )

= ln (e^x+1) - ln (x^3 + x^2)

= (x+1) ln e - ln ((x^2(x+1))

-can't get past this point. - Nov 5th 2007, 03:26 AMtopsquark
What do you mean by "verified?"

We can go a few more steps:

$\displaystyle = (x+1) ln(e) - ln (x^2(x+1)) $

$\displaystyle = (x+1) ln(e) - ln (x^2) - ln(x+1) $

$\displaystyle = (x+1) ln(e) - 2ln (x) - ln(x+1) $

and since $\displaystyle ln(e) = 1$,

$\displaystyle = (x+1) - 2ln (x) - ln(x+1) $

-Dan - Nov 5th 2007, 03:33 AMGAdams
I guess verify here means show that it is the same as?

- Nov 5th 2007, 04:00 AMtopsquark